Development of Student Worksheets (LKPD) based on Project Based Learning in Vocational Basic Lessons to Improve Creativity of Vocational School Students - Agustina, Livianti; Marsono, Marsono; Widiyanti, Widiyanti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to develop Project Based LKPD Learning (PJBL) on basic vocational subjects of financial accounting and institutions that are valid, effective and practical in improving student learning outcomes. This study uses the research and development (R & D) method using a 4-D model. This model consists of 4 stages of development, namely defining, designing, developing, and disseminating. The product developed is in the form of Project Based Learning (PJBL)-based LKPD which is tested through validity tests, effectiveness tests and tests practicality. The subjects in this study were students of class X AKL SMK Negeri 1 Pagerwojo, Tulungagung for the academic year 2021/2022 as many as 115 students. The instrument used in data collection is a validation sheet for knowing the level of validity of the developed LKPD obtained from a team of experts, learning outcomes test to determine the effectiveness of LKPD and student response questionnaires as well as a teacher response questionnaire to determine the level of practicality of the LKPD that developed. The results showed that LKPD based on Project Based Learning (PJBL) on the basic vocational subjects of financial accounting and institutions that the researchers developed have a level of validity by a team of material experts and valid design experts, namely 3.28 assessment of student responses and teacher responses, the level of practicality of teaching materials is in the positive category with an average total score of 3.5. Learning outcomes test using Project-based worksheets.